NOVOS COMPOSTOS DE COORDENAÇÃO ENTRE O FLAVONÓIDE HESPERDINA E ÍONS METÁLICOS DE RELEVÂNCIA BIOINORGÂNICA - Faganello, N. L.; Teixeira, E. I.; Pinheiro, A. C. N.; Gonçalves, A.; Cruz, M. M.; Biscoli, L. O.; Facco, J. T.; dos Anjos, A. (ANAIS DO ENIC, 2017)
-